Systemic interaction between educators of choreographic disciplines under distance learning conditions - Olha Yatsenko; Ilona Khomiachyk; Liudmyla Hladka; Nadiia Vasina; Natalia Koresandovych; Nataliia Slupska (Universidad de Murcia, 2022)
Article accepted. The article will be published here soon. Pending final quality checks.